(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: On April 24, 2013, Rana Plaza, an 8 storied building accommodating 5 garment factories, a bank, a number of commercial shops and offices collapsed at Savar, Dhaka, Bangladesh, while more than 4 thousand people were working inside. A massive rescue operation was carried out in following 21 days by the Government of Bangladesh involving all of her associated organs with a key role played by the Armed Forces. A total of 2438 injured victims were rescued between 24 Apr 2013 and 10 May 2013 including a female garment worker who was rescued after 17 days of the building collapse. The death toll finally reached to 1132 including 2 rescue workers. This unprecedented disaster was mitigated by extraordinary responses from almost all the organs of government and also from non-government bodies. All available medical resources were utilized for immediate, short term and long term management of the injured victims. Objective: This study is aimed to find out the pattern of injuries in the victims of this catastrophe and also the management of mass casualty in Rana Plaza tragedy which occurred due to the multistoried commercial building collapse. Methods: This observational study was conducted on pre-hospital, in-hospital and post-hospital management of the victims of the disaster. Each of the injured individuals was tracked for a period of more than 3 months. Data were collected from interviews, observation and by studying the records of field medical units, secondary and tertiary hospitals and rehabilitation centres. Results: This was the deadliest garments factory accident in the history causing 1132 deaths and 2438 injured cases. The rescue operation was carried out upto 14 May 2013. Removal of the whole collapsed building rubbles took 21 days and 1127 dead bodies had been recovered. Two rescuers died during rescue operation. Out of 2438 casualties 407 were brought to SMH Savar, 28 victims of serious injury were evacuated to CMH Dhaka where only one patient died. One thousand and seven hundred casualties were taken to Enam Medical College and Hospital, Savar and 105 patients were taken to National Institute of Traumatology and Rehabilitation (NITOR). Two hundred and twenty six patients received management in the other private clinics. Out of 2438 patients, 951 received prolonged hospital treatment of which blunt trauma was found in 225(23.66%) cases, soft tissue injuries in 149(15.67%) cases, fractures in 137(14.41%) cases, crush syndrome in 46(4.84%), head injuries in 40(4.20%), limb loss in 33(3.47%) and other non lethal injuries were observed in 321(33.75) cases. Three patients expired during treatment due to complications like acute renal failure, ARDS and complication of head injury. Up to 26 Jul 2013, 36 cases were found disabled to sequelae of head injury, spinal injury, fracture of long bones of limbs and injury of peripheral nerves. Among the patients of mass casualty commonest complication or presentation was acute stress reaction in 44.92 percent of patients. Conclusion: Management of mass casualty in this building collapse provides us with a valuable experience which may be utilized in dealing with similar disasters that might take place in any densely populated city in an earthquake prone country like Bangladesh. DOI: http://dx.doi.org/10.3329/jafmc.v9i2.21819 Journal of Armed Forces Medical College Bangladesh Vol.9(2) 2013